Geo-informatics based groundwater plan preparation of Kichna nala watershed of Odisha - PAUL, J. C.; PANIGRAHI, B.; PADHI, G. C.; MISHRA, P. (Journal of Soil and Water Conservation, 2020)
Remote sensing and geographical information system (GIS) technique have been applied for the investigation of groundwater potentiality of the Kichna nala watershed in Bamara block of Sambalpur District (Odisha), where ground water resources have not been fully exploited. The role of various parameters namely drainage, lineament, land cover, geomorphology have been emphasized for delineation of ground water potential zones. IRS-ID LISS-III FCC merged satellite images on 1:50,000 scale and toposheet map number 73 C/05 together with field verification have been used as the data source. Different thematic maps like, geomorphology, drainage and surface water body, land use/ land cover, etc. were prepared by various integration and finally all these map were analysed in GIS to prepare an integrated ground water potential map of the study area with five different ground water potential zones. Analysing the lineament intersection points and ground verification in the watershed, 18 sites have been selected and suggested for tube well construction with their latitude and longitude.